(NsTRATIFORMNOE SWINCOWO(B-(NCINKOWOE ORUDENENIE u^KULA^SKOGO RUDNOGO POLQ (B/s - (NpANKRATXEW(B, (NpETR wLADIMIROWI^s; (NhAMRABAEW(B, (Ni(B.(Nh(B.s; (NaKADEMIQ NAUK uZssrs; (NiNSTITUT GEOLOGII I GEOFIZIKI IM(B. (Nh(B.(Nm(B. (NaBDULLAEWA an uZssrs ((NtA[KENT (B:s (NfAN (B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 226-282s
Keywords: (NgEOFIZIKAs; (NsWINCOWO(B-(NCINKOWYE MESTOROVDENIQ STRATIFORMNYEs -- (NsREDNQQ aZIQs